Heath-related quality of life in Spanish breast cancer patients: a systematic review - López-Abente Gonzalo; Forjaz Maria; Pollán Marina; García-Mendizábal María; Delgado-Sanz María; Aragonés Nuria; Pérez-Gómez Beatriz (Health and Quality of Life Outcomes, 2011)
Abstract Background Breast cancer is one of the oncological diseases in which health-related quality of life (HRQL) has been most studied. This is mainly due to its high incidence and survival. This paper seeks to: review published research into HRQL among women with breast cancer in Spain; analyse the characteristics of these studies; and describe the instruments used and main results reported. Methods The databases consulted were MEDLINE, EMBASE, PsycINFO, Dialnet, IBECS, CUIDEN, ISOC and LILACS. The inclusion criteria required studies to: 1) include Spanish patients, and a breakdown of results where other types of tumours and/or women from other countries were also included; and, 2) furnish original data and measure HRQL using a purpose-designed questionnaire. The methodological quality of studies was assessed. Results Spain ranked midway in the European Union in terms of the number of studies conducted on the HRQL of breast cancer patients. Of the total of 133 papers published from 1993 to 2009, 25 met the inclusion criteria. Among them, only 12 were considered as having good or excellent quality. A total of 2236 women participated in the studies analysed. In descending order of frequency, the questionnaires used were the EORTC, FACT-B, QL-CA-Afex, SF-12, FLIC, RSCL and CCV. Five papers focused on validation or adaptation of questionnaires. Most papers examined HRQL in terms of type of treatment. Few differences were detected by type of chemotherapy, with the single exception of worse results among younger women treated with radiotherapy. In the short term, better results were reported for all HRQL components by women undergoing conservative rather than radical surgery. Presence of lymphedema was associated with worse HRQL. Three studies assessed differences in HRQL by patients' psychological traits. Psychosocial disorder and level of depression and anxiety, regardless of treatment or disease stage, worsened HRQL. In addition, there was a positive effect among patients who reported having a "fighting spirit" and using "denial" as a defence mechanism. One study found that breast cancer patients scored worse than did healthy women on almost all SF-12 scales. Conclusion Research into health-related quality of life of breast-cancer patients is a little developed field in Spain.